2008
DOI: 10.1016/j.cell.2008.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Undertaker, a Drosophila Junctophilin, Links Draper-Mediated Phagocytosis and Calcium Homeostasis

Abstract: Phagocytosis is important during development and in the immune response for the removal of apoptotic cells and pathogens, yet its molecular mechanisms are poorly understood. In Caenorhabditis elegans, the CED2/5/10/12 pathway regulates actin during phagocytosis of apoptotic cells, whereas the role of the CED1/6/7 pathway in phagocytosis is unclear. We report that Undertaker (UTA), a Drosophila Junctophilin protein, is required for Draper (CED-1 homolog)-mediated phagocytosis. Junctophilins couple Ca2+ channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 47 publications
10
151
0
Order By: Relevance
“…3C). Furthermore, the requirement of Draper in the phagocytosis of S. aureus in adult flies (40) was confirmed in our in vivo assay (data not shown). On the other hand, a lack of Draper did not influence the phagocytosis of latex beads both in vitro by larval hemocytes and in vivo by adult flies (data not shown), showing that Draper is not required for the basal phagocytic activity of hemocytes.…”
Section: Mediation Of Ltas-dependent Phagocytosis Of S Aureus By Drapersupporting
confidence: 51%
See 1 more Smart Citation
“…3C). Furthermore, the requirement of Draper in the phagocytosis of S. aureus in adult flies (40) was confirmed in our in vivo assay (data not shown). On the other hand, a lack of Draper did not influence the phagocytosis of latex beads both in vitro by larval hemocytes and in vivo by adult flies (data not shown), showing that Draper is not required for the basal phagocytic activity of hemocytes.…”
Section: Mediation Of Ltas-dependent Phagocytosis Of S Aureus By Drapersupporting
confidence: 51%
“…We then tested Draper, another Drosophila protein that contains the NIM repeat, which has been known as a receptor for the phagocytosis of apoptotic cells (26,29) and neuronal axons (38,39). More recently, the involvement of Draper in the phagocytosis of S. aureus in adult flies was reported (40). The level of phagocytosis of RN4220 by hemocytes prepared from the larvae of a draper null mutant was about one-third to half of that by hemocytes of w 1118 (Fig.…”
Section: Mediation Of Ltas-dependent Phagocytosis Of S Aureus By Drapermentioning
confidence: 99%
“…As the histograms and RMFI values show (Figure 4), NimC1 bound to E. coli with the highest RMFI value, comparable to that for the Draper receptor used as positive control, as it was previously shown that the loss of Draper function inhibits the phagocytosis of E. coli [8,21]. NimB1 bound E. coli with lower RMFI.…”
Section: Nimrod Proteins Selectively Bind Bacteriamentioning
confidence: 61%
“…A direct link between InsP 3 -mediated Ca 2ϩ release and SOCE has been contested in vertebrates based primarily on data from DT40 cells in which all three InsP 3 Rs have been deleted (Broad et al, 2001;Ma et al, 2002). Interestingly, in Drosophila macrophages, SOCE through dOrai is coupled to intracellular Ca 2ϩ release through the ryanodine receptor (RyR; Cuttell et al, 2008). Thus in Drosophila there appears to exist cell-type-specific coupling of either InsP 3 R-or RyR-mediated Ca 2ϩ -release to SOCE.…”
Section: Correlating Intracellular Calcium Homeostasis With Flight Bementioning
confidence: 99%